Pengaruh Tarif dan Kualitas Pelayanan Terhadap Kepuasan Konsumen (Studi Pada CV. Noria Jaya Abadi Amat Rental Semarang) - Aditya Utama Putra; Agus Hermani; Sri Suryoko (Jurnal Ilmu Administrasi Bisnis, 2014)
Population growth will increase the demand, both qualitatively and quantitatively. Vehicle needs is increasingly rising, they want things to be practical and easy, so they choose a car to transport all members of his family or in a vehicle. In this case the customer satisfaction is a matter that greatly affect the growth and development of the car rental company. The level of customer satisfaction with a product will give a reflection of success in producing a good company, because if a product will be a failure if the product or service does not provide satisfaction for its users. One of them is to provide customer satisfaction is the application of rates, so that may affect the price of the car rental. Quality of service is also very important because the quality of service is work performed by the employees to serve the customers in order to feel comfortable             This study aims to determine the effect of variable rates and quality service to customer satisfaction on the CV. Noria Amat Rental Jaya Abadi Semarang. The population of this research is the customer's CV. Noria Jaya Abadi Rental Amat, and the sample amounted to 80 respondents. Measurement scale using a Likert scale. Analysis of the data using linear regression analysis.             From the analysis of the data can be concluded that the effect on the variable rates of 30.6 percent consumer satisfaction. Variables affect the Quality of Service Customer Satisfaction by 40 percent. Together Rates and Service Quality effect on Consumer Satisfaction by 71.1 percent.             Based on these results, it is suggested CV management. Noria Jaya Abadi Amat Rental Rates need to consider the application of the Company's need to increase the price reduction when renting for longer, should the rate increase dimbangi with benefits and facilities that will be obtained by the customers. Quality Service Employees need to be considered, especially the attitude of the driver and the office staff to be more friendly, more friendly manner, then the customer is expected to feel valued and respected, timeliness fleet still sometimes late so that potential customers waiting fleet longer, it can be detrimental to a candidate so that the potential customer to switch to another rental, use of an entertainment facility (audio, CD room, and TVs) are still rarely used because there are parts of the device is damaged to be repaired